Vận dụng tâm lý học vào hoạt động thanh tra - Trần, Hậu Kiêm (2011)
Tác giả: Trần Hậu Kiêm, PTS; Nguyễn Đình Xuân, CN; Phạm Viết Khẩu, CN; Nguyễn Hữu Đàn, CN; Chu Minh Hảo, CN; Phạm Đăng Dũng, CN; Nguyễn Đức Hướng, CN -- Từ khóa: Thanh tra; Tâm lý học; Tâm lý xã hội; Cán bộ thanh tra